Identification of Phenotypes in People with COPD: Influence of Physical Activity, Sedentary Behaviour, Body Composition and Skeletal Muscle Strength - Xavier, Rafaella F.; Pereira, Ana Carolina A. C.; Lopes, Aline C.; Cavalheri, Vinicius; Pinto, Regina M. C.; Cukier, Alberto; Ramos, Ercy M. C. [UNESP]; Carvalho, Celso R. F. (Springer, 2019)
Introduction People with chronic obstructive pulmonary disease (COPD) present high prevalence of physical inactivity that leads to a negative effect on health-related quality of life (HRQoL). The present study investigated COPD phenotypes according to their levels of physical activity and sedentary behaviour, as well as body composition and skeletal muscle strength. Methods This is an observational and cross-sectional study. Anthropometric data and COPD clinical control were collected and all participants underwent assessments of lung function, HRQoL, dyspnoea, levels of physical activity and sedentary behaviour, body composition and skeletal muscle strength. Participants were classified using hierarchical cluster analysis. Age, dyspnoea and obstruction (ADO) index was used to determine prognosis and calculated for each cluster. Results One hundred and fifty-two participants were included. Three distinct phenotypes were identified. Participants in phenotype 1 were more physically active, less sedentary and had better body composition and lower ADO index (p < 0.0001 for all variables). Overall, participants in phenotypes 2 and 3 were less physically active, more sedentary having a higher ADO index. However, participants in phenotype 2 were older, whereas participants in phenotype 3 had worse HRQoL, clinical control and body composition. Lung function did not differ across the three phenotypes. Conclusions Our results show that physical activity, sedentary behaviour and body composition should be considered to determine phenotypes in people with COPD and are involved in the prognosis of the disease. Less sedentary patients have better prognosis while age, body composition and clinical control seems to differentiate physically inactive patients.
Keywords: Daily life physical activity; Muscle mass; Health-related quality of life; Prognosis